2013
DOI: 10.1186/1749-7922-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of the injury pattern in severely injured patients with an associated clavicle fracture: a retrospective observational cohort study

Abstract: BackgroundDespite an increasing interest in the treatment of clavicle fractures, this is still a not yet defined area in severely injured patients as most studies exclude these patients. Analyzing fracture type and evaluate accompanying injuries can provide valuable information in an early stage of trauma care.ObjectiveTo identify prevalence, fracture type and accompanying injuries of clavicle fractures in the severely injured patient.MethodsWe included all severely injured patients (ISS ≥ 16) with a clavicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
9
1
2
Order By: Relevance
“…The increasing incidence of clavicle fractures has led to increases in the rates of clavicle nerve injury, numbness, and pain after open reduction and internal fixation. [ 15 , 16 ] However, the prognosis of patients with numbness after surgery remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing incidence of clavicle fractures has led to increases in the rates of clavicle nerve injury, numbness, and pain after open reduction and internal fixation. [ 15 , 16 ] However, the prognosis of patients with numbness after surgery remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of skull fractures, skull APs are taken more frequently than clavicle X-rays. Van Laarhoven et al [ 12 ] reported that a skull fracture is the most commonly associated injury in severely injured patients with clavicle fractures. Thus, physicians should maintain a high index of suspicion for clavicle fractures when they read a skull AP because of the frequency with which skull APs are performed and the association between skull and clavicle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Blunt thoracic trauma contributes to complications and mortality as it may directly injure vital thoracic and abdominal structures secured by the chest wall, but also secondarily by impairing the chest wall integrity [3][4][5][6]. Both clavicle fractures and rib fractures have been shown to act as a marker of severity of the chest injury and have both independently been shown to increase the risk of mortality [7][8][9][10][11]. A combination of clavicle and rib fractures may further worsen the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have shown benefits of operative treatment of multiple displaced rib fractures and flail chest injuries, compared to conservative treatment [16][17][18][19]. More than 10% of polytrauma patients suffer from a clavicle fracture, with 77% of those also sustaining other thoracic injuries [9]. Treatment of isolated clavicle fractures primarily depends on the location, displacement, and degree of comminution of the fracture [20,21].…”
Section: Introductionmentioning
confidence: 99%